Science, technological innovation and entrepreneurship - Pezo Paredes, Alfredo (2010)
Between the fifties and seventies of the last century, the economic and productive debate related development with growth; today we resume the discussion aware of the need to produce with the highest possible added value and that this requires prioritizing science and technology. The CEPLAN proposals and the PNCTI 2006-2021 coincide in highlighting the strategic importance of science, technology and innovation in Peru's competitive development. But innovation is not enough; an entrepreneurial culture is also necessary; unfortunately, Peru occupies one of the most unfavorable positions in the world in terms of the business environment for local entrepreneurs.